Law and Religion: Destruction and Reconstruction (Stato, Chiese e pluralismo confessionale, 2024)
Diritto e religione: decostruzione e ricostruzioneABSTRACT. In the 1940s, Austrian economic Joseph Schumpeter coined the concept of “creative destruction” to describe how capitalism evolves through the relentless and continuous dismantling of its old paradigms. Fast forward to the present, British and American scholars Russell Sandberg and Marc O. De Girolami are emerging today as contemporary “creative destroyers” in the field of law and religion. Pointing to the pathologies affecting the intellectual development of the discipline and prescribing possible remedies, this paper introduces and discusses two recent works by the Authors as part of their efforts to critically deconstruct law and religion and project it into the future.SUMMARY: 1. Introduction - 2. Repentance - 3. Reappraisal- 4. Regeneration - 5. Discussion - 6. Death and New Life - 7. Conclusions.